Effect of T6 heat treatment on Mechanical Properties of Aluminium Alloy; ADC10 - Supatthana, Krisada; Hirunyagird, Jirutthitikalpongsri (Food Agricultural Sciences and Technology, 2019)
This research aims to study of effect T6 heat treatment on microstructure and mechanical property of aluminum alloy; ADC 10 and using master alloy as 5Ti-1B. Master alloys were added as 0, 0.02, 0.04, 0.06 and 0.08 %wt. Aluminum alloy was melted at 750 ± 10 ºC by induction furnace and then pouring molten metal into a permanent mold where the temperature is 240 ± 10 ºC. And then, solution treatment at 548 o C for 1 hr; quenching in water. Aging temperature at 204 o C for 1 hr. The results showed that adding 5Ti-1B as 0.08% after T6 process with the highest hardness and tensile strength were 41.13 HRB and 254.79 MPa, respectively. Impact energy was 3.1 J. The microstructure results showed that the refi nement by adding 5Ti-1B 0.02-0.80%wt affect the grain size. Moreover, the addition of 5Ti-1B 0.08 %wt results in fi ne grain and uniform distribution. XRD results confi rmed the formation of Al2 Cu from precipitation in aging process have indicated the presence of Al2 Cu peaks distribution in matrix. As a result, aluminum alloy; ADC 10 has higher mechanical properties.